2022
DOI: 10.1097/qai.0000000000002880
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Nicotine Metabolism Ratio Increases in HIV-Positive Smokers on Effective Antiretroviral Therapy: A Cohort Study

Abstract: Background: People with HIV (PWH) smoke tobacco at much higher rates than the general population. Previous research has shown that PWH have faster nicotine metabolism than HIVuninfected individuals, which may underlie this disparity, but the cause is unknown. We investigated whether higher nicotine metabolite ratio (NMR; 3-hydroxycotinine:cotinine), a validated biomarker of nicotine metabolism through CYP2A6, was associated with antiretroviral use among HIV-infected smokers. Methods:We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…A handful of studies in the general population demonstrated a relationship between high NMR and older age [ 24 , 26 , 31 ]. However, studies in HIV populations did not report these associations [ 11 , 30 ], which was consistent with our findings. We also found no association with sex, which was inconsistent with existing evidence showing that women have a higher NMR than men [ 18 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A handful of studies in the general population demonstrated a relationship between high NMR and older age [ 24 , 26 , 31 ]. However, studies in HIV populations did not report these associations [ 11 , 30 ], which was consistent with our findings. We also found no association with sex, which was inconsistent with existing evidence showing that women have a higher NMR than men [ 18 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the values of NMR found in our study sample were lower than what was reported in other populations of PWH in high-resource settings; however, the existing evidence came largely from more diverse Western settings, with a large proportion of participants of Caucasian descent. Mean values of NMR in literature among PWH range from 0.35 to 0.47 [ 11 , 25 , 27 , 30 ], whereas the mean in this study was 0.32. Given our sample was entirely Black South African, and given African Americans on average have a lower NMR than other racial/ethnic groups, the homogeneity of our population, with a genetic makeup closer to those with typically lower NMRs, aligned our findings with these other studies.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, efavirenz is associated with a higher NMR in PWH. 12,16 Schnoll et al found that NMR in PWH on efavirenz-containing regimens was 0.67 compared with 0.44 in those on non-efavirenz-containing ART. As efavirenz is known to induce CYP2A6 24 -the predominant liver enzyme responsible for nicotine metabolism-our study adds further evidence that ART associated with HIV treatment, rather than HIV itself, may explain the higher nicotine metabolism rates seen in other cohorts of PWH.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of nicotine metabolism among PWH may be due to direct viral effects of HIV itself, metabolic effects on the liver due to HIV infection or viral hepatitis, or pharmacologic effects of ART. [13][14][15][16] Direct virologic effects may induce CYP2A6 activity and thus increase NMR. CYP2A6 activity can be induced by inflammation and has been found to be higher in persons with hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…11 A recent study found that in PWH who achieved viral suppression on ART, those who took ART regimens including efavirenz had a higher mean NMR increase than those on regimens without efavirenz. 10 Given the likely effect of efavirenz on CYP2A6 activity, we hypothesized stopping efavirenz-based therapy would result in decreases in the NMR.…”
Section: How Might This Change Clinical Pharma-cology or Translationa...mentioning
confidence: 99%